Mauritius : 2011 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
Over the past two decades, wide-ranging structural reforms, supported by prudent policies, have established Mauritius as a top regional performer. The Mauritian economy recovered in 2010. Real GDP growth is estimated to have accelerated to 4 percent (3 percent in 2009), driven by strong growth in fishing, ICT, and financial industries. Against the backdrop of the European debt crisis and a depreciating Euro in mid-2010, the government adopted a second stimulus package. Fiscal policy was less expansionary than originally envisaged.